Analisis Peranan Pemerintah Terhadap Praktik Greenwashing Dalam Strategi Investasi Keuangan Berkelanjutan Berbasis ESG - Chandra, Julius Adi Chandra; Rian Sacipto; muktiono, Muktiono (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2022)
Sustainable Finance is one of the government's steps in preserving the Environment. A concrete form of sustainable finance is an ESG-based sustainable investment. Financial Service Institutions, Issuers, Banks, and Public Companies are required to implement Sustainable Finance in order to achieve a national economy that grows stably, inclusively, and sustainably and can prevent forms of investment in business activities that use excessive resources that have the potential to damage the Environment, these demands are based on POJK Number 51 /POJK.03/2017. However, the regulation still does not regulate specific classifications and indicators for companies that do use nature as one of their business prospects, as a result of which Greenwashing practices often occur indirectly. Therefore, according to the author, OJK as an institution in charge of regulating and supervising financial services activities in the Banking sector, Capital Market sector, and IKNB sector, must make special arrangements related to Greenwashing practices so as to eliminate ambiguity in implementing Sustainable Finance in ESG-based Sustainability Investment strategies.